Novel pre-clinical mouse models for chronic Graft-versus-Host Disease - Verlaat, Lydia; Riesner, Katarina; Kalupa, Martina; Jung, Beate; Mertlitz, Sarah; Schwarz, Constanze; Mengwasser, Jörg; Fricke, Claudine; Penack, Olaf (Frontiers in Immunology, 2023)
Despite considerable progress in allogeneic hematopoietic stem cell transplantation (allo-HSCT) has been achieved over the past years, chronic Graft-versus-Host Disease (cGvHD) still contributes to high morbidity rates, thus remaining a major hurdle in allo-HSCT patients. To understand the complex pathophysiology of cGvHD and to develop refined prophylaxis and treatment strategies, improved pre-clinical models are needed. In this study, we developed two murine cGvHD models, which display high long-term morbidity but low mortality and depict the heterogeneous clinical manifestations of cGvHD seen in patients. We established a haploidentical C57/BL6 > B6D2F1 allo-HSCT model that uses myeloablative radiation and G-CSF-mobilized splenocytes as stem cell source and a sub-lethally irradiated Xenograft model, which utilizes the transfer of human peripheral blood mononuclear cells (PBMCs) into NOD scid gamma (NSG)-recipients. We characterized both mouse models to exhibit diverse clinical and histopathological signs of human cGvHD as extensive tissue damage, fibrosis/ sclerosis, inflammation and B cell infiltration in cGvHD target organs skin, liver, lung and colon and found a decelerated immune cell reconstitution in the late phase after HSCT. Our pre-clinical models can help to gain a deeper understanding of the target structures and mechanisms of cGvHD pathology and may enable a more reliable translation of experimental findings into the human setting of allo-HSCT.